Beyond contracted prices: determinants of agility in government electronic procurement - Reis, Paulo Ricardo da Costa (2018)
Studies on the effectiveness of government procurement have a prominent focus on contracted prices. However, not much is known about other dimensions of the performance of contracts awarded by the government such as the relation of interdependence between contracted prices and quality. Using delivery time as a dimension for quality, this study explores the mechanisms that influence contracted prices and delivery time. It also discusses how price reduction influences ex-post quality in the context of government electronic procurement. Analysis using a data base with detailed information of 3,755 procurement processes executed by a Brazilian organization of the Federal Public Administration shows that, despite procurement processes being effective to reduce prices in competitive bids, there is no evidence that this price reduction negatively affects delivery time. In addition, results show that suppliers with a history of poor performance are those that keep harming government procurement performance.